Advances in Experimental Medicine and Biology
DOI: 10.1007/0-306-46840-9_20
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Regulatory Cross-talk Between the Decay Accelerating Factor-binding Fimbrial/Afimbrial Adhesins and Type I Fimbriae

Abstract: The revised sequence of DaaA means that the protein is 98% identical to the afimbrial adhesin regulator AFAA-III. While PapB repressed FimB OFF to ON switching in strain AAEC370A, this was not the case for DaaA. PapB, but not DaaA, reduced the level of expression of type 1 fimbriae, in static LB media. Attention is now focused on the amino terminus of the PapB protein as the possible domain involved in cross talk with type 1 fimbriae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…These organisms may carry the determinants for several fimbrial and afimbrial adhesins (19). The members of the Afa/Dr family of adhesins, including Dr, Dr-II, AFA I, AFA III, and F1845, have similar genetic organization (32) and recognize DAF as a receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…These organisms may carry the determinants for several fimbrial and afimbrial adhesins (19). The members of the Afa/Dr family of adhesins, including Dr, Dr-II, AFA I, AFA III, and F1845, have similar genetic organization (32) and recognize DAF as a receptor (31).…”
Section: Discussionmentioning
confidence: 99%
“…Site-directed mutagenesis introducing a limited number of mutations into the open reading frame, designated daaP, appears to show that a sequence of the DaaP peptide is important and that translation of the daaP gene is required in cis to promote processing by the endonuclease. Interestingly, whereas PapB lowered the level of expression of type 1 fimbriae, DaaA did not (192). Adhesin F1845 has 57% identity with Dr adhesin (91 amino acids out of 160 are identical) (340).…”
Section: Adhesin F1845mentioning
confidence: 99%
“…Preliminary data suggested that DaaA did not repress type 1 fimbriae (Holden et al ., 2000), and the results here show that the majority of PapB analogues also do not share this specific ability; exceptions being SfaB and PefB that have the highest homology to PapB and were capable of partially repressing type 1 fimbriae expression. The amino and carboxy termini of PapB are unique by comparison with the rest of this regulator family (Fig.…”
Section: Introductionmentioning
confidence: 99%